2008
DOI: 10.2139/ssrn.1102543
|View full text |Cite
|
Sign up to set email alerts
|

Creditor Rights and Debt Allocation within Multinationals

Abstract: We analyze the optimal debt structure of multinational corporations choosing between centralized or decentralized borrowing. We identify how this choice is affected by creditor rights and bankruptcy costs, taking into account managerial incentives and coinsurance considerations. We find that partially centralized borrowing structures are optimal with either weak or strong creditor rights. For intermediate levels of creditor rights fully decentralized (centralized) borrowing structures are optimal if managers h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Akbel and Schnitzer (2011) take into consideration the legal environment to analyze the decision of a multinational enterprise to choose between centralized (parental) or decentralized borrowing (local). The study by Desai et al (2008) find that parent firms which are exposed to significant foreign political risk use less leverage.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Akbel and Schnitzer (2011) take into consideration the legal environment to analyze the decision of a multinational enterprise to choose between centralized (parental) or decentralized borrowing (local). The study by Desai et al (2008) find that parent firms which are exposed to significant foreign political risk use less leverage.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Aulakh and Mudambi (2005) find that flows from subsidiary to the headquarter decreases with growing concentration and growth in the industry to which the subsidiary belongs. Akbel and Schnitzer (2011) examine industry-level patterns and observe that MNCs operating in industries with long-term pay-off periods prefer a centralized borrowing structure (parent borrowing).…”
Section: Industry-based View and Financing Of Ofdimentioning
confidence: 99%
“…4 It is assumed that borrowing costs depend only on local debt ratios, not on the total debt ratio, which ist most likely to happen under decentralized borrowing or in the absence of any guarantee of the parent company. Although Inderst and Muller¨ (2003) and, more recently, Akbel and Schnitzer (2011) showed that decentralized borrowing may indeed have its merits, my interpretation here is simply that a guarantee by the parent company is not credible.…”
Section: Introductionmentioning
confidence: 80%
“…The fact that board members of multinationals and banks are from the same social and political network and judicial environment reduces uncertainty and subsequently risk exposure when multinationals are expanding abroad. For example, Akbel and Schnitzer () identify how the choice of MNEs between centralised or decentralised borrowing is affected by the legal environment(s) – i.e. creditor rights and bankruptcy costs – of the countries in which a MNE's subsidiaries operate.…”
Section: Literature Reviewmentioning
confidence: 99%